The last outlaw - Bittner, Rosanne, 1945- (Bittner, Rosanne, 1945- Outlaw hearts, 2017)
"Times have changed, and the old Wild West is a thing of the past. Nestled in his beautiful Colorado ranch, surrounded by family, infamous former outlaw Jake Harkner's hung up his guns for good and finally found a measure of peace--but dark memories haunt the woman who has always been his strength, and not even Jake is certain he can save his beloved Miranda this time. All he can do is swear to remain by her side. But it takes more than a hope for peace to outrun a past defined by violence, and it isn't long before Jake is embroiled in a rescue mission he simply can't refuse. Life has brought him back full circle as he rides into Mexico to save a young girl from a dreadful fate... leaving Miranda behind one final time, fearing that the man she loves more than anything is destined to die the way he's always lived--by the gun."--Amazon.com.